Katz-Wachtel phenomenon in an adult with dilated cardiomyopathy - Dinkar Bhasin; Ayush Agarwal; Yash Paul Sharma; Arun Sharma; Soumitra Ghosh (Wolters Kluwer Medknow Publications, 2023)
Katz-Wachtel phenomenon is an electrocardiogram (ECG) sign demonstrating large equiphasic precordial QRS complexes indicative of biventricular hypertrophy. This sign is most commonly seen in children with congenital heart disease and is rarely described in adults. We report a case where this ECG sign was noted in an adult with dilated cardiomyopathy and discuss the possible mechanisms for this unusual finding.